2017
DOI: 10.1590/1678-4685-gmb-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Defense-related proteins involved in sugarcane responses to biotic stress

Abstract: Sugarcane is one of the most important agricultural crops in the world. However, pathogen infection and herbivore attack cause constant losses in yield. Plants respond to pathogen infection by inducing the expression of several protein types, such as glucanases, chitinases, thaumatins, peptidase inhibitors, defensins, catalases and glycoproteins. Proteins induced by pathogenesis are directly or indirectly involved in plant defense, leading to pathogen death or inducing other plant defense responses. Several of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 155 publications
(211 reference statements)
0
27
0
3
Order By: Relevance
“…[38] GLU belongs to PR protein, which can inhibit pathogen growth by degrading the cell wall of pathogenic fungi or indirectly activate defense responses by releasing excitons from the cell wall. [39] A similar study also found that GLU inhibits the oxidative damage and enhances the tolerance of plant toward pathogen infection. [40] In the present result, GLU activity in peaches treated with P. guilliermondii increased during the entire storage period, thereby indicating the activation of the essential defense reactions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[38] GLU belongs to PR protein, which can inhibit pathogen growth by degrading the cell wall of pathogenic fungi or indirectly activate defense responses by releasing excitons from the cell wall. [39] A similar study also found that GLU inhibits the oxidative damage and enhances the tolerance of plant toward pathogen infection. [40] In the present result, GLU activity in peaches treated with P. guilliermondii increased during the entire storage period, thereby indicating the activation of the essential defense reactions.…”
Section: Discussionmentioning
confidence: 76%
“…PR proteins were divided into 17 different families, among which PR2 and PR3 were defined as GLU and CHI, which inhibit pathogen growth by degrading the cell wall. [24] PR1, as the marker of disease resistance, is associated with SAR. [5] PRs play a prominent part in the resistance of fruits under environmental stress at the micromolar level.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts, including the use of pathogenesisrelated proteins, have been made to overcome pathogenic fungi in crop plants (Souza et al, 2017). Khan et al (2016) reported the development of Rhizoctonia solani-resistant potato plants through the genetic transformation of the chitinase II gene.…”
Section: Discussionmentioning
confidence: 99%
“…As proteínas PR já foram identificadas em resposta a infecção por fungos, oomicetos, bactérias e vírus, e a ataques de insetos e nematódeos (Cornelis van Loon, 1999;Souza et al, 2017;van Loon et al, 2006). Essas proteínas também foram detectadas em plantas após aplicação de substâncias que mimetizassem o efeito de ataque por um patógeno ou em resposta a injúrias que produzissem proteínas que se acumulam durante uma infecção (Sels et al, 2008).…”
Section: Normalização Dos Dados De Expressão Gênica Gerados Por unclassified
“…Inibidores de peptidases apresentam indução transcricional após inoculação com microrganismos, ataque de inseto e injúria. Também foi observada atividade antifúngica, in vitro, para uma proteína desse grupo, assim como aumento da resistência a patógeno de uma linhagem transgênica de A. thaliana que apresentava expressão aumentada de um gene PR6 endógeno (Chassot et al, 2007;Sels et al, 2008;Souza et al, 2017).…”
Section: Normalização Dos Dados De Expressão Gênica Gerados Por unclassified